The issues of the implementation of the Certificate of Completion and Compliance (CCC) in Klang Valley / Siti Shamsiah Hashim Baki - Hashim Baki, Siti Shamsiah (Faculty of Architecture, Planning and Surveying, 2014)
Prior to 2007, the building was completed only be entered or occupied when the Certificate of Fitness or Certificate of Fitness (CF) issued by the Local Authorities (LAs) to developers or owners. Normally, developers have difficulties obtaining CF for various reasons and excuses. To overcome this problem, the government has introduced a new method in delivery system namely Certificate of Completion and Compliance (CCC) which is the certificate issued by the professional known as Principal Submitting Person (PSP) who has major roles such as submit building plans to the LA for approval. However, after 7 years CCC is implemented, there have several problems arise such as CCC varies from one local authority to another, too much checklist and the procedure are complicated. The data analysis is to achieve 3 objectives of this study mainly are to examine the problems occurs in CCC implementation and to give recommendations on how to overcome the current problems in CCC implementation. To collect and analyse the data, interviews and questionnaire survey was conducted and quantitative data obtained from 50 respondents from the OSC staff and officers, LA and PSP.